Pendidikan Islam Multikultural diSekolah - Dwiyani, Aryanti (Darajat: Jurnal Pendidikan Agama Islam, 2023)
This paper examines the problem of multicultural Islamic education in public schools byprioritizing religious, cultural and social values in schools, students can have anunderstanding of religion, diversity and differences in life. The importance of multiculturalIslamic education is taught in public schools, especially in the era of globalization marked byadvances in science and technology that have had a positive impact on life. However, on theother hand, this progress has had a negative impact on the lives of students. The occurrence ofexclusive attitudes and a lack of understanding of differences, diversity, tolerance andmoderation of religions, including understanding religious values in the lives of students,causes multicultural values in schools to fade and disappear. The methodology used is observation, interviews and documentation and is supported by various relevant references sothat it has scientific value in research. This paper attempts to provide an offer or solution"how is multicultural Islamic education taught in schools so as to form an inclusive (open),tolerant pattern of religious understanding for students. Multicultural Islamic education istaught in public schools emphasizing recognition and respect for differences that areinevitable for people of any religion and improving from a strong emphasis on the cognitivedomain to the affective and psychomotor domains as well as improving the quality of teachersboth from the standpoint of their understanding of their own religion and other religions, sothat they themselves have the right perspective of multiculturalism. Therefore. MulticulturalIslamic education is taught in public schools, especially at SMA Negeri 2 Mataram.